2019
DOI: 10.1111/ijlh.13047
|View full text |Cite
|
Sign up to set email alerts
|

Flow cytometry “Ogata score” for the diagnosis of myelodysplastic syndromes in a real‐life setting. A Latin American experience

Abstract: Introduction Flow cytometry (FC) is a helpful tool for the diagnosis of myelodysplastic syndrome (MDS). Different FC score systems have been developed. The “Ogata score” is a simple diagnostic score that has been validated having a sensitivity of 69% and a specificity of 92% in low‐risk MDS. We aimed to study the feasibility and the utility of the “Ogata score” for the diagnosis of MDS among Latin America (LA) Laboratories. Methods This is a case and control study conducted in LA institutions members of Grupo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…Thus, our results confirm the test performance described by Cremers and colleagues (Cremers et al, 2017). In line with the literature, Ogata-score, RED-score, and ELN-NEC also revealed a very high specificity (Della Porta et al, 2012;Grille Montauban et al, 2019;Mathis et al, 2013;Ogata et al, 2009;Westers et al, 2017). However, probably due to their focus on a single cell compartment (progenitors or NEC) sensitivity of these FCM-scores is lower.…”
Section: Impact Of Ifs On Overall Survival (Os)supporting
confidence: 92%
“…Thus, our results confirm the test performance described by Cremers and colleagues (Cremers et al, 2017). In line with the literature, Ogata-score, RED-score, and ELN-NEC also revealed a very high specificity (Della Porta et al, 2012;Grille Montauban et al, 2019;Mathis et al, 2013;Ogata et al, 2009;Westers et al, 2017). However, probably due to their focus on a single cell compartment (progenitors or NEC) sensitivity of these FCM-scores is lower.…”
Section: Impact Of Ifs On Overall Survival (Os)supporting
confidence: 92%
“…MFC will complement the primary morphological evaluation, especially in borderline cases where immunophenotypic aberrations can support or exclude MDS diagnosis (as illustrated in a diagnostic algorithm presented in Figure 1 in . The previous iMDSflow recommendation that the four-parameter Ogata score (Ogata et al, 2009) may be used for a preliminary assessment of MFC dysplasia has been confirmed by several publications (Bardet et al, 2015;Dhingra et al, 2020;Grille Montauban et al, 2019;Kárai et al, 2017;Mannelli et al, 2019;Matzen et al, 2018;Muyldermans et al, 2019;. This score is based on the frequency of myeloid CD34 + myeloid progenitors (MP) (>2%), the fraction of B-cell precursors within CD34 + cells (<5%), abnormal CD45 expression on CD34 + blasts, and low granulocyte scatter (granulocyte/lymphocyte SSC ratio ≤6).…”
Section: Minimal Requirements To Assess Dysplasia By Mfcmentioning
confidence: 97%
“…Multiple reports from various countries have confirmed the diagnostic value of iMDSFlow recommendations (Chauhan et al, 2021;Cremers et al, 2016;Cremers et al, 2017;Davydova et al, 2021;Grille Montauban et al, 2019;Majcherek et al, 2021;Takeuchi et al, 2020). However, results of a survey concerning current MFC practice in 229 laboratories around the world showed that although many laboratories used large numbers of markers in MFC workup of MDS (median: 20 ± 4.5), the compliance with iMDSflow recommendations was low, and proposed scoring systems were not widely applied (Grille Montauban et al, 2019;Jensen et al, 2019). With the hope of increasing the harmonization of MFC MDS diagnostics, the current paper presents a summary of the progress in this field and an update on consensus iMDSFlow guidelines for the assessment of significant anomalies in various bone marrow (BM) cell compartments for MFC features of dysplasia as a part of a special Issue of Clinical Cytometry B, focused on MFC applications in MDS and MDS/MPN (Kern et al, 2022;van der Velden et al, 2023;Wagner-Ballon et al, 2023;Westers et al, 2021;Westers et al, 2023).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Em primeiro lugar, confirmamos o valor prognóstico do aumento dos progenitores mielóides CD34 + e diminuição dos progenitores de células B, o que já foi descrito por nosso grupo (21,29,45) e também por outros (15,22,27,46,47).…”
Section: Discussionunclassified